The The Influence of Brand Image and Sharia Promotion on the Community's Decision to Become Members of BMT UGT Nusantara Capem Tegaldlimo Banyuwangi - Niswatummajidah, Elok; Kanzul Fikri, Muhammad (Dinasti Publisher, 2025)
This study aims to determine the effect of brand image and sharia promotion on people's decisions to become members of KSPPS BMT UGT Nusantara Capem Tegaldlimo. This study uses a quantitative approach with data collection using a questionnaire. The sampling method in this study used random sampling with a sample size of 60 members of KSPPS BMT UGT Nusantara Capem Tegaldlimo. The accumulation of data used in this study is primary data from the questionnaire. The data analysis method used is Validity Test, Reliability Test, Classical Assumption Test (normality test, heteroscedasticity test, and multicollinearity test) and multiple linear regression (t test, f test, r2 determination). The partial test results show that the t-value x1 is 4.743 > t-table value 2.002 and x2 t-value 2.428 > t-table value 2.002, meaning that brand image and sharia promotion have a significant effect on the decision to become a member of KSPPS BMT UGT Nusantara Capem Tegaldlimo and simultaneously show a calculated f-value of 56.893 > f-table value 3.16, so brand image and sharia promotion have a significant effect on the decision to become a member of KSPPS BMT UGT Nusantara Capem Tegaldlimo.